2D III‐Nitride Materials: Properties, Growth, and Applications. Issue 27 (28th May 2021) - Ben, Jianwei; Liu, Xinke; Wang, Cong; Zhang, Yupeng; Shi, Zhiming; Jia, Yuping; Zhang, Shanli; Zhang, Han; Yu, Wenjie; Li, Dabing; Sun, Xiaojuan
Abstract: 2D III‐nitride materials have been receiving considerable attention recently due to their excellent physicochemical properties, such as high stability, wide and tunable bandgap, and magnetism. Therefore, 2D III‐nitride materials can be applied in various fields, such as electronic and photoelectric devices, spin‐based devices, and gas detectors. Although the developments of 2D h‐BN materials have been successful, the fabrication of other 2D III‐nitride materials, such as 2D h‐AlN, h‐GaN, and h‐InN, are still far from satisfactory, which limits the practical applications of these materials. In this review, recent advances in the properties, growth methods, and potential applications of 2D III‐nitride materials are summarized. The properties of the 2D III‐nitride materials are mainly obtained by first‐principles calculations because of the difficulties in the growth and characterizations of these materials. The discussion on the growth of 2D III‐nitride materials is focused on 2D h‐BN and h‐AlN, as the developments of 2D h‐GaN and h‐InN are yet to be realized. Therefore, applications have been realized mostly based on the 2D h‐BN materials; however, many potential applications are cited for the entire range of 2D III‐nitride materials. Finally, future research directions and prospects in this field are also discussed. Abstract : The graphene‐like 2D III‐nitride semiconductor materials have unique physical properties such as high stability, wide and tunable bandgap, and magnetism, etc. Those advantages prove them to be useful in optoelectronic, electronic, and spin‐based devices and so on. The pro perties, growth methods, and applications of graphene‐like 2D III‐nitride materials are introduced and reviewed.